Instrumented open-source filament extruder for research and education - de Oliveira Filho, Maurício [UNESP]; de Jesus, Matheus Cerqueira [UNESP]; Nakazato, Anderson Zenken [UNESP]; Kondo, Marcel Yuzo [UNESP]; de Oliveira Hein, Luis Rogerio [UNESP] (Elsevier, 2022)
Extruders are necessary equipment for 3D filament manufacturing, which is considered a clean technology because it has less scrap and can reuse materials, increasing its life cycle. Open source extruders are less expensive than industrial extruders. However, they have little instrumentation, which limits processing analysis and thus the development of new materials, screw design and process control. Therefore, this project aims to develop a low-cost extruder with a high degree of instrumentation for in-situ process analysis. To achieve this, equipment was developed with an integrated circuit board, both with modularity, machine and peripheral control, process stability, and data acquisition. To validate the equipment, processing was done at constant temperature and with flow variation. The data obtained were the temperatures at different points in the barrel, the rotation speed of the extruder motor, the current consumed by the motor and the resistances, and the speed of the extruder motor. Thermal images of the components were obtained during processing, validating the type of material used in the parts manufactured by additive manufacturing. The ABS filament produced was analyzed by flow and surface analysis using a confocal microscope. Higher flow rates had a better surface quality of the filament.
Keywords: Circular economy; Filament quality; In situ process; Pilot plant